W poszukiwaniu językowego pierwowzoru wizerunku czeladnika piwowarskiego = In search of a linguistic prototype for the image of a brewing journeyman - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article has been devoted to the analysis of the circles of meaning "honesty", "modesty", "decency" and "piety", as well as the collocations and contexts of the use of lexemes evoking them in social and fraternity articles of the Krakow brewers` guild from the 17th and 18th centuries. It can be observed that lawmakers are mainly interested in such personality traits that allow for the safe and efficient functioning of corporations.
Keywords: historia języka polskiego; cech; wspólnota towarzyska (czeladników); wzór osobowy; leksyka wartościująca; history of the Polish language; guilds; social (journeymen) community; personal pattern; evaluative lexicon